2015
DOI: 10.1016/j.rcae.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice manual: Postoperative controls

Abstract: a b s t r a c t Introduction: Post-anesthetic care reduces the anesthesia-related postoperative complications and mortality, shortens the length of stay at the postoperative care units and improves patient satisfaction.Objective: To establish a set of recommendations for immediate post-anesthetic care of patients that received general/regional anesthesia or profound/moderate sedation at the postoperative care units.Methodology: This is a process of "rapid" clinical practice guidelines adaptation, including sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 83 publications
0
2
1
Order By: Relevance
“…As for complications such as hypothermia, hypovolemia, fever or kidney failure, they were observed by other authors but are not among the ones reported in this research. However, the "pain" variable, despite being the second most frequent complication, was not prevalent compared to the findings of other authors, whose study results presented 75% of patients reporting pain in the postoperative period (Caro et al, 2015). It is important to point out that, for the highest rate of performed procedures, 39.6% (143), no mentions of presence or absence of complications were found in the patients' medical records, which suggests a need for greater caution and attention from health professionals as to adding this information to said documents.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…As for complications such as hypothermia, hypovolemia, fever or kidney failure, they were observed by other authors but are not among the ones reported in this research. However, the "pain" variable, despite being the second most frequent complication, was not prevalent compared to the findings of other authors, whose study results presented 75% of patients reporting pain in the postoperative period (Caro et al, 2015). It is important to point out that, for the highest rate of performed procedures, 39.6% (143), no mentions of presence or absence of complications were found in the patients' medical records, which suggests a need for greater caution and attention from health professionals as to adding this information to said documents.…”
Section: Resultscontrasting
confidence: 72%
“…In this research, the most frequent postoperative complication was hypotension, with 8.6% (31), followed by pain, with 6.4% (23), twice the percentage reported by Caro et al (2015) in their study.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation